The story of "me" : contemporary American autofiction - Worthington, Marjorie (Lincoln : University of Nebraska Press, 2018)
"The Story of "Me" shows that the burgeoning of autofiction serves as a barometer of American literature from modernist authorial effacement to postmodern literary self-consciousness"--
Introduction: Autofiction in an American Context -- 1. Masculinity, Whiteness, and Postmodern Self-Consciousness: Vladimir Nabokov, John Barth, Kurt Vonnegut, and Richard Powers -- 2. Rage Against the Dying of the Author: Philip Roth, Arthur Phillips, Ruth Ozeki, Salvador Plascencia, and Percival Everett -- 3. The New Journalism as the New Fiction, The New Subjectivity as The New Objectivity: Tom Wolfe, Norman Mailer, Hunter S. Thompson, Joan Didion, Mark Leyner, and Bret Easton Ellis -- 4. Trauma Autofiction, Dissociation, and the Authenticity of "Real" Experience: Kurt Vonnegut, Raymond Federman, Tim O'Brien and Jonathan Safran Foer -- 5. Memoir vs. Autofiction as The Story of Me vs. The Story of "Me": Philip Roth, Richard Powers, Bret Easton Ellis, and Ron Currie Jr. -- Coda -- Appendix: American Autofictions.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on December 06, 2018).
eBooks on EBSCOhost
Keywords: Autobiographical fiction -- History and criticism; American fiction -- 20th century -- History and criticism; American fiction -- 21st century -- History and criticism; Autobiography in literature; Self in literature; Postmodernism (Literature) -- United States; Roman américain -- 20e siècle -- Histoire et critique; Roman américain -- 21e siècle -- Histoire et critique; Autobiographie dans la littérature.; Moi (Psychologie) dans la littérature.; Postmodernisme (Littérature) -- États-Unis.; LITERARY CRITICISM -- American -- General; American fiction; Autobiographical fiction; Autobiography in literature; Postmodernism (Literature); Self in literature; United States; Autobiografische Literatur; Autobiografischer Roman; Selbstdarstellung; USA; 1900-2099; Electronic books; Criticism, interpretation, etc